Psychological Stress among Mothers of Autistic Children in light of the Counseling Services provided to them in Al-Madinah Al-Munawarah - Al-Mutairi, Waad AbdulKarim (Journal of Educational and Psychological Sciences, 2024)
The main purpose of this study is to investigate the level of psychological stress of the mothers with children having autism spectrum disorder (ASD). It also aims to examine the effectiveness of the advisory services provided by the special day care centers in Al-Madinah Al-Munawarah. The researcher applied an experimental qualitative research design. Six mothers of children with ASD attending the special day care center in Madinah have participated in the study. Participants were asked to take part in a clinical interview and to fill out an observation card. The thematic analysis technique was used to analyze the collected data. This study found that Four mothers who participated in this study are suffering from a high level of psychological stress whereas two mothers have a low-level of psychological stress. Most mothers also asserted that they have received an average level of advisory services including emotional and psychological support, training sessions to increase awareness about ASD’s conditions, and guidance and assistance for its therapy.